PELAKSANAAN E-GOVERNMENT PADA APLIKASI SISTEM INFORMASI KELUHAN MASYARAKAT ONLINE (SIKESAL) DI KOTA JAMBI TAHUN 2018-2019 - Ahmad, Zakly Hanafi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Online Community Complaints Information System or Sikesal is an E-Government program that functions as a place for complaints and aspirations submitted by the people of Jambi City regarding improvements or problems with public services. The problem in this study is that the implementation of the Sikesal application in Jambi City has not been optimal due to several determining factors that underlie the readiness of implementing E-Government that have not been achieved. The purpose of this study is to determine the implementation of E-Government in the Sikesal application in Jambi City 2018-2019.This study uses Indrajit's theory, which is related to the determining factors for the readiness of implementing E-Government in the regions. The research approach used is a qualitative approach. This type of research is descriptive. The research location is in Jambi City, to be precise at the Communication & Informatics Office as well as several agencies that have the most reports on this Sikesal application. Types and sources of research data are divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to the Sikesal application.The results of this study are that the implementation of E-Government in the Sikesal application by the Jambi City Government in 2018-2019 is not optimal, this is because the level of E-Government readiness is only fulfilled in two indicators, namely telecommunications infrastructure, and paradigm shift. The obstacles that underlie the process of implementing this system are related to the implementation process that has not been evaluated, so there are several obstacles that are different from other implementing agencies, the absence of a special budget for the application socialization program so that many people do not know about this application and still report with the manual method, as well as the role of the heads of agencies in the regions who seem not yet serious in supporting the implementation of E-Government because they are preoccupied with their respective internal affairs.Â Keywords: Implementation of Sikesal, Kominfo, Indicators